1982
DOI: 10.1111/j.1476-5381.1982.tb09325.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Amfonelic Acid and Some Other Central Stimulants on Mouse Striatal Tyramine, Dopamine and Homovanillic Acid

Abstract: 1 The concentrations of p-and m-tyramine, dopamine and homovanillic acid were measured in the mouse striatum following the subcutaneous administration of amfonelic acid, (+)-amphetamine or nomifensine.2 The administration of 2.5-25 mg/kg of amfonelic acid produced a reduction in p-tyramine that lasted at least 8 h. m-Tyramine was significantly increased and this was observed between 2 and 24 h after drug treatment. The levels of homovanillic acid were increased within 4 h after amfonelic acid administration.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Amfonelic acid, which has structural analogies to ofloxacin, has been developed by Sterling-Winthrop as a psychostimulant ( Va/li and Bouyard, 1978). However, despite the chemical analogy, their effects -at least on monaminergic processes -do not seem to be identical (Juorio, 1982). It has been reported that a number of quinolones, especially ciprofloxacin (Ciprobay®), norfloxacin (Barazan®), enoxacin, pipemidic acid, and ofloxacin inhibit the binding of GABA in iso-Iated rat neurons (Hori et al, 1985(Hori et al, , 1986.…”
Section: Discussionmentioning
confidence: 99%
“…Amfonelic acid, which has structural analogies to ofloxacin, has been developed by Sterling-Winthrop as a psychostimulant ( Va/li and Bouyard, 1978). However, despite the chemical analogy, their effects -at least on monaminergic processes -do not seem to be identical (Juorio, 1982). It has been reported that a number of quinolones, especially ciprofloxacin (Ciprobay®), norfloxacin (Barazan®), enoxacin, pipemidic acid, and ofloxacin inhibit the binding of GABA in iso-Iated rat neurons (Hori et al, 1985(Hori et al, , 1986.…”
Section: Discussionmentioning
confidence: 99%
“…HVA has been recognized and utilized as a biomarker of various diseases and as a target molecule to measure the overall dopamine activity in the human body since the 1970s. 3,4 Therefore, the determination of HVA concentration in plasma, urine, or cerebrospinal fluid is related to diagnosis, disease progress monitoring, and drug dose optimization. 5,6 Cancer of adrenal medullary pheochromocytoma and neuroblastoma and neurological diseases such as post-traumatic stress disorder are related to the increase of HVA concentration in body fluid.…”
Section: Introductionmentioning
confidence: 99%
“…306-08-1, white crystalline powder, and its chemical structure is presented in Figure ) is a metabolite of catecholamine. , It is mainly derived from the whole grass and root of the dicotyledonous plant Paeoniaceae. HVA has been recognized and utilized as a biomarker of various diseases and as a target molecule to measure the overall dopamine activity in the human body since the 1970s. , Therefore, the determination of HVA concentration in plasma, urine, or cerebrospinal fluid is related to diagnosis, disease progress monitoring, and drug dose optimization. , Cancer of adrenal medullary pheochromocytoma and neuroblastoma and neurological diseases such as post-traumatic stress disorder are related to the increase of HVA concentration in body fluid. However, the decrease of HVA concentration is a typical symptom of depression and Parkinson’s disease. , …”
Section: Introductionmentioning
confidence: 99%